Predictive Implications of Dynamic Factors on Investors Decision in Indian Derivatives Market: An Empirical Study - Tsegenet Mengistu Abebe; Prafulla Kumar Swain; Rabinarayan Patnaik; Manoj Kumar Sahoo (The Bioscan, 2025)
Since the Indian derivative market is growing rapidly and participation in retail increases, the study investigates factors that affect investment decisions of retail investors. Despite market growth, investor behaviours is understood, especially in emerging economies. This study examines risk tolerance, financial literacy, market dynamics, regulatory environment and how technology/access affects investment decisions to fill this difference. The study uses a quantitative explanation-induced design, with a structured questionnaire distributed to 129 retail investors. We used convenience sampling and online recruitment to increase demographic diversity. Data analysis used descriptive and subordinate figures such as Piercen's correlation and several linear regressions to determine variable conditions. The results suggest that technology/access (β = 0.250, p = 0.002) and economic literacy (β = 0.207, p = 0.014) are the leading prophecies for investment decisions. Regulatory Environment (β = 0.184, p = 0.028) and risk tolerance (β = 0.161, p = 0.049) Make considerable impact.. The model has a strong fit, explaining 76.2% of investment decision variance (Adj. R² = 0.752, F = 77.917, p < 0.001). Conclusions emphasize the requirement for integrated guidelines to improve financial literacy, technical access, and regulatory framework. The results point to integrated policies needed to improve regulatory systems, tech access, and financial education. The findings highlight the need of comprehensive policies meant to improve regulatory systems, technology accessibility, and financial literacy.